Arabic as a Compulsory Language in Pesantren - Nur, Nuti Nawaty; Nurhalimah, Iid Khadijah; Kirom, Abd.; Bidari, Bidari; Qibtiyah, Luthfatul (Universitas Al-Amien Prenduan, 2024)
This study aims to explain Arabic language learning as a compulsory communication language in pesantren. Arabic has a central role in daily activities in pesantren, both in the learning process and in social interactions between students. This research uses a qualitative approach with a case study type, which involves observation and interviews. The object in this research is intensive female students of University of Al-Amien Prenduan. The results showed that University of Al-Amien Prenduan campus is a campus that creates a foreign language environment. Arabic language learning does not only occur formally but also occurs non-formally through language programs. In addition, the support of a conducive environment and intensive language practice also accelerate the mastery of Arabic by the students. Thus, Arabic becomes an essential communication tool in shaping the character and increasing the scientific competence of santri in pesantren. This study concludes that learning Arabic as a compulsory communication language in pesantren is very effective in improving the language skills and religious understanding of santri.